Designing an Institute with Research Approach in the Field of the Pharmacy Issues at University - Mostafavipoor, Seyed Mehrdad; Pourebtehaj, Ali; Chini, Reyhaneh; Barzegar, Alireza; Mohagheghzade, Abdolali (International Pharmacy Acta, 2018)
Introduction: With the emergence of new challenges in the field of pharmacy, the identity of this field and its vital role in the health system of the country, dealing with these challenges and making appropriate and strategic decisions is necessary. Hence, designing student based centers, focusing on research with strategic and national approach, and the purpose of educating students to help decision-makings in the pharmaceutical community can be beneficial. Methods and Results: The Pharmaceutical Strategic Studies Office established with the aim of knowing and studying on the drug and pharmaceutical issues nationally and strategically, using data collected from the Ministry of Health, Food and Drug organization, Medical Sciences universities, research centers and pharmaceutical companies. This office, in the format of professional workgroups, collects required information through research projects, workshops, holding seminars and scientific visits and present them along with suggesting solutions for improving the health status of the community and the position of the pharmacist in new formats such as professional meetings with the competent and decision maker authorities. The mentioned idea has led to the attraction of about 100 students in the format of 12 workgroups of career opportunities, education, Pharmaceutical Organizations in the World and Iran, economy and industry, laws, service centers, human resources estimation, ethics, socio-cultural, media, medicinal plants and future studies. The information of workgroup were gathered through 30 specialized workshops and seminar meetings, 3 special workshops for students and teachers of Education and Training General Office, scientific visits from policy-making institutions, scientific and industrial institutions of Tehran, Isfahan, Mashhad and Shiraz cities; And their results were presented through holding two specialized congresses on the challenges of pharmaceutical and bioethics with the presence of professors and national authorities. Conclusions: It is a necessity to design the student base centers such as the Pharmaceutical Strategic Studies Office focusing on national providential researches and strategic thinking, in order to learn decision-making and help the executing authorities of the country by modern methods and eliminate the absence of thinking in the universities, it will be possible to achieve the main objective of the advancement in medicine and pharmacy.